Student’s Perspective on the use Gamification in Improving English Vocabulary - Sinaga, Suryani Martalia; Manurung, Agatha; Napitupulu, Angelica; Silalahi, Dumaris E. (Universitas Pahlawan Tuanku Tambusai, 2025)
The integration of technology in language learning has revolutionized traditional teaching methods, particularly in vocabulary acquisition. This study investigates students' perspectives on using gamification, specifically Kahoot!, in improving English vocabulary among tenth-grade students at SMA Negeri 3 Pematangsiantar. The research addresses the gap between conventional vocabulary teaching methods and the need for engaging, technology-enhanced learning experiences. Through a qualitative approach involving 35 participants over a one-week intensive observation period, this study employed interviews, questionnaires, and classroom observations to gather data. The findings reveal that 85% of students demonstrated increased motivation and engagement when learning vocabulary through Kahoot!, with 78% reporting improved retention of new words. Students particularly appreciated the competitive elements and immediate feedback features of the platform. The study concludes that gamification through Kahoot! positively influences students' vocabulary learning experience, suggesting its potential as an effective supplementary tool in English language education. However, considerations regarding technical infrastructure and careful implementation planning are necessary for optimal results.